The Uncertainty and Countermeasures of General Anti-Avoidance Clause - Dian Zhu; Yuanyuan Peng (Law and Economy, 2023)
The Article 47 of the Enterprise Income Tax Law introduces the general anti-tax avoidance clause, and gradually constructs the general anti-tax avoidance rule system around the clause. General anti-tax avoidance provisions play an important role in making up for the deficiency of special anti-tax avoidance provisions in anti-tax avoidance. However, due to the unreasonable legislative provisions of general anti-tax avoidance provisions and the lack of judicial supervision of the administration-led anti-tax avoidance model, the tax authorities lack guidance in applying these rules, which leads to the uncertainty of the application of general anti-tax avoidance provisions. This article analyzes the causes of the uncertainty of general anti-tax avoidance provisions from the legislative, administrative and judicial aspects, and puts forward suggestions to solve the uncertainty caused by the legislation and application of general anti-tax avoidance provisions.